2019
DOI: 10.3390/su11092615
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Financial Market Investors Attitudes toward Corporate Social Responsibility: Evidence from Mergers and Acquisitions

Abstract: As China’s economic development has shifted from quantitative growth to qualitative improvement, stakeholders have enforced stricter corporate social responsibility (CSR) requirements for listed companies. However, few studies have focused on companies and CSR in such developing economies. We used the CSR scoring system from Hexun Finance’s website to group Chinese listed companies according to their CSR scores. By comparing the effects of merger and acquisition (M&A) announcements on different CSR scores,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
(81 reference statements)
2
13
0
Order By: Relevance
“…[15] found that high-CSR acquirers achieve higher M&A announcement return, greater post-M&A long-term operating performance growth, and positive long-term stock return. Similar viewpoint was also held by [14] who found that acquirers with low-CSR performance tend to obtain longer term abnormal returns.…”
Section: Literature and Hypothesissupporting
confidence: 71%
See 1 more Smart Citation
“…[15] found that high-CSR acquirers achieve higher M&A announcement return, greater post-M&A long-term operating performance growth, and positive long-term stock return. Similar viewpoint was also held by [14] who found that acquirers with low-CSR performance tend to obtain longer term abnormal returns.…”
Section: Literature and Hypothesissupporting
confidence: 71%
“…While prior M&A literature has looked into the impact of CSR on pre-and post-M&A corporate performance [14], M&A duration [15], choice of acquisition target [16,17] and shareholder value of the acquirer [14,15,18], and socially responsible companies are believed to have higher economic performance and firm value [5,6,8], whether and how the CSR performance of the acquirer and that of the target are valued during the acquisition process is a problem that remains unsettled.…”
Section: Introductionmentioning
confidence: 99%
“…Data on CSR scores came from Hexun (HX) listed company's social responsibility report which is the first vertical financial portal website in China. The database provides financial information services as well as annual ratings for CSR strengths and concerns under several categories [70][71][72].…”
Section: Sample and Methodsmentioning
confidence: 99%
“…Cash compensation requires the shareholders of the original bid purchased to pay cash to the listed enterprise. However, when the shareholders cannot provide so much cash, they will use the shares to compensate the listed enterprise through bottoming clauses [ 26 ]. In the way of equity compensation, the amount of consideration to be compensated needs to be divided by the unit price of the shares at the time of the M&A transaction to obtain the number of shares to be compensated.…”
Section: Methodsmentioning
confidence: 99%